Vectorial approach to coupled nonlinear Schrödinger systems under nonlocal Cauchy conditions. Issue 4 (2nd April 2016) - Bunoiu, Renata; Precup, Radu
Abstract : The paper presents a vectorial approach for coupled general nonlinear Schrödinger systems with nonlocal Cauchy conditions. Based on fixed-point principles, the use of matrices with spectral radius less than one, and on basic properties of the Schrödinger solution operator, several existence results are obtained. The essential role of the support of the nonlocal Cauchy condition is emphasized and fully exploited.